Improving purchasing performance in a new product development context - A case study at a research and development organisation - Frödell, Lina; Skovshoved, Maja (My University, 2017)
Purchasing processes exists in all organisations today, and are seldom connected to one department. Instead, several departments are included in the decisions on what to buy, which can make the process very complex. Dependence relationships occurs between the included departments, and an efficient communication is a prerequisite to achieve high purchasing performance. This thesis is made in collaboration with a purchasing division in a research and development company, which struggles to achieve on time deliveries on their orders. They are to a great extent dependent on information from other departments in the organisation which increases the complexity of their activities. This creates a situation where the buyers have problems to place orders to suppliers on time, which consequently causes late deliveries of the material to the R&D projects. The purpose of this thesis was to improve the purchasing process at the purchasing division in the organisation to be more efficient and contribute to on time deliveries. To achieve this, the process was mapped and analysed to detect areas of improvement, and dependent input from other departments was defined. To fulfil the purpose, empirical data of the current situation was collected through direct observations, semi-structured interviews, and internal documents. Further, to create an understanding of activities in the purchasing process three specific components with different characteristics were studied and analysed. Several wastes could be identified in the processes, they were categorised in their difficulty to be implemented and their effect on the process time and purchasing performance. Suggestions of improvements regarding the processes was produced to reduce the prioritised waste, and the focus were on how to coordinate the interface between Material & Logistics and the other departments, and how the work processes and input could be standardised. The suggestions of improvement made it possible to save time in the processes, these savings were explained and visualised in future state maps. This contributed to an understanding of how the current situation at the organisation could be changed to improve the purchasing process. When compressing time the efficiency can be increased and this gives a better opportunity to reach on time deliveries, which continuously increase the purchasing performance.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics